2015
DOI: 10.1007/s10620-015-3651-7
|View full text |Cite
|
Sign up to set email alerts
|

Foods Provoking and Alleviating Symptoms in Gastroparesis: Patient Experiences

Abstract: This study identified specific foods that worsen as well as foods that may help alleviate symptoms of gastroparesis. Foods that provoked symptoms differed in quality from foods that alleviated symptoms or were tolerable. The results of this study illustrate specific examples of foods that aggravate or improve symptoms and provide suggestions for a gastroparesis diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…A study of 45 patients identified that foods provoking symptoms, such as orange juice, fried chicken, cabbage, oranges, sausage, pizza, peppers, onions, tomato juice, lettuce, coffee, salsa, broccoli, bacon, and roast beef, were generally fatty, acidic, spicy, and roughage-based. 29 A high-fat solid meal significantly increased overall symptoms among individuals with gastroparesis. 30 On the other hand, saltine crackers, jello, and graham crackers moderately improved symptoms, and 12 additional foods were tolerated without provoking symptoms.…”
Section: Advances In Dietary Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 45 patients identified that foods provoking symptoms, such as orange juice, fried chicken, cabbage, oranges, sausage, pizza, peppers, onions, tomato juice, lettuce, coffee, salsa, broccoli, bacon, and roast beef, were generally fatty, acidic, spicy, and roughage-based. 29 A high-fat solid meal significantly increased overall symptoms among individuals with gastroparesis. 30 On the other hand, saltine crackers, jello, and graham crackers moderately improved symptoms, and 12 additional foods were tolerated without provoking symptoms.…”
Section: Advances In Dietary Recommendationsmentioning
confidence: 99%
“…These were: ginger ale, gluten-free foods, tea, sweet potatoes, pretzels, white fish, clear soup, salmon, potatoes, white rice, popsicles, and applesauce. 29 …”
Section: Advances In Dietary Recommendationsmentioning
confidence: 99%
“…Wytiaz et al [25] studied selfreported aggravation or alleviation by nutrients in 45 patients with gastroparesis (39 idiopathic), using food toleration and aversion rating questionnaires. Patients reported food substances, which they considered to aggravate (orange juice, fried chicken, cabbage, oranges, sausage, pizza, peppers, onions, tomato juice, lettuce, coffee, salsa, broccoli, bacon, and roast beef) or improve (saltine crackers, jello, and graham crackers) symptoms, and indicated good tolerance for a number of food items (ginger ale, gluten-free foods, tea, sweet potatoes, pretzels, white fish, clear soup, salmon, potatoes, white rice, popsicles, and applesauce) [25]. These data can be used as a basis for designing dietary interventions in gastroparesis.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…In addition, the skins prevent moisture loss from the scale surface and reduce respiration rate (Apeland, 1971). Although onion skins play an important role in postharvest onion storage and shelf life, knowledge of their formation is limited (Hole et al, 2002).…”
Section: Introductionmentioning
confidence: 99%